Dry mortar compositions containing metal salts of polyols
By using cement binder, polyol metal salt, foreign alumina source and ettringite formation control agent in the dry mortar composition, the problems of unstable settling time and aging in the cement flowing mortar are solved, and stable storage is achieved and high strength dry mortar composition.
Patent Information
- Application Number
- CN202380039368.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-09
- Filing Date
- 2023-05-02
- Publication Date
- 2024-12-20
AI Technical Summary
In the application of cement flow mortar, the solidification time of the existing dry mortar composition is unstable and prone to aging, resulting in an accelerated hydration speed and a sharp decrease in ease during storage, making it difficult to meet the solid and constant hardening requirements.
Using dry mortar compositions containing cement binders, metal salts of polyols, foreign alumina sources, sulfate sources and ettringite formation control agents, ensure that the composition is stored during storage by specific component ratios and additions. Constant stability and solidification time.
The constant solidification time and high comprehensive strength of the dry mortar composition are achieved, ensuring that there is no aging during storage, and it can be stored stably for several months, while providing good hardening performance after mixing.
Smart Images

Figure BDA0005125393690000021 
Figure BDA0005125393690000022 
Figure BDA0005125393690000061
Abstract
Description
[0001] The present invention relates to a dry mortar composition, the dry mortar composition comprising: (a) a cement binder, the cement binder comprising one or more calcium silicate mineral phases and one or more calcium aluminate mineral phases, (b) a metal salt of a polyol; (c) an optional external alumina source; (d) a sulfate source; and an ettringite formation control agent, the ettringite formation control agent comprising. The present invention also relates to a mixed mortar composition comprising the dry mortar composition and water and a product obtained from the mixed mortar composition.
[0002] Polyols, especially glycerol, are the raw materials in many dry mortars. However, because glycerol is a liquid rather than a solid, it must be present in powder form.
[0003] WO2020 / 0173723A1 discloses a building material comprising a mixture containing at least one compound A selected from glyoxylic acid, its salts and condensation or addition products of glyoxylic acid or its salts; and at least one polyhydroxy compound B.
[0004] WO 2022 / 043347 A describes a building composition comprising a cement binder, optionally an external aluminate source, a sulfate source, an ettringite formation controller and a polyol.
[0005] In WO 2022 / 043348 A1, a cement-reduced building composition is described, which comprises a cement binder, fines, a polyol, an ettringite formation controller and a co-retarder.
[0006] WO2022 / 043349A1 discloses a limestone calcined cement building composition, which comprises a cement binder, a supplementary cement material, an optional external aluminate source; a sulfate source, a polyol, an ettringite former and a co-retarder.
[0007] In WO 2022 / 043350 A1, a building composition is described, which contains a cement binder comprising one or more calcium silicate mineral phases and one or more calcium aluminate mineral phases; an optional external aluminate source; a sulfate source; and a setting control composition comprising a polyol.
[0008] In the application of cementitious flowing screeds, strong and constant hardening is an important criterion. Systems that harden faster over time are more difficult for the processor to handle.
[0009] Pure spraying onto cement surfaces or dry mortar mixes is not feasible, as this would lead to strong aging effects of the dry mortar during storage in cement bags or silos. The hydration rate would then be greatly accelerated and workability would drop sharply over time.
[0010] It is therefore an object of the present invention to provide a dry mortar composition having a constant setting time while exhibiting comparable overall strength.
[0011] Surprisingly, it was found that the above object can be solved by the following method:
[0012] Item 1: A dry mortar composition, comprising
[0013] (a) a cementitious binder comprising one or more calcium silicate mineral phases and one or more calcium aluminate mineral phases,
[0014] (b) a metal salt of a polyol, wherein the polyol is selected from a monosaccharide, an oligosaccharide, a water-soluble polysaccharide, a compound of the general formula (PI), or a dimer or trimer of a compound of the general formula (PI):
[0015]
[0016] where X is
[0017]
[0018] in
[0019] R 1 is -H, -CH3;
[0020] R 2 is -H, -CH3;
[0021] R 3 are -CH2OH, -NH2;
[0022] R 4 Yes -H, -(CH2) p CH2OH, -(CH2) s CH(OH)CH3;
[0023] m is an integer from 1 to 4;
[0024] n is an integer from 1 to 8;
[0025] p is an integer from 1 to 4;
[0026] s is an integer from 1 to 4;
[0027] (c) optionally an external source of alumina;
[0028] (d) a sulfate source;
[0029] wherein the composition comprises
[0030] (e) available aluminate from said calcium aluminate mineral phase plus said optional external aluminate source, in the form of Al(OH)4 per 100 g of cement binder a). - Calculated, the total amount is at least 0.05 mol;
[0031] and a molar ratio of total available aluminate to sulfate of 0.4 to 2.0;
[0032] The composition also comprises
[0033] (f) an ettringite formation controlling agent, the ettringite formation controlling agent comprising (i) glyoxylic acid, a glyoxylate, a hydroxycarboxylic acid or a derivative or salt thereof and / or a glyoxylic acid derivative and a salt thereof; and / or
[0034] A mixture of the above substances, and (ii) a carbonate source, wherein the carbonate source is selected from inorganic carbonates, preferably having a carbonic acid content of 0.1 g·L at 25°C. -1 or higher water solubility; organic carbonates; and mixtures thereof.
[0035] Item 2: The composition according to Item 1, wherein the composition further comprises a co-retarder (g), wherein the co-retarder is selected from (g-1) phosphonic acid and its salts, (g-2) polycarboxylic acid and its salts; and mixtures thereof.
[0036] Item 3: A composition according to Item 1 or 2, wherein the composition further comprises (h) fine material having a Dv90 of less than 200 μm, preferably less than 150 μm, selected from alkali-activatable binders, rock powders and inorganic pigments or mixtures thereof, in a total amount of 20 to 200 parts by weight relative to 100 parts by weight of cement binder (a).
[0037] Item 4: The composition according to any one of the preceding items, wherein the metal salt of the polyol (b) is present in an amount of 0.15 wt % to 2.5 wt % relative to the amount of the cement binder (a).
[0038] Item 5: The composition according to any one of the preceding items, wherein the calcium salt of the polyol (b) is present in a crystalline or amorphous form.
[0039] Item 6: A composition according to any one of the preceding items, wherein the metal salt (b) of the polyol is a calcium salt of a compound of general formula (PI) or a dimer or trimer of a compound of general formula (PI), preferably a calcium salt of a compound of general formula (P-Ia), more preferably calcium glycerate or a calcium salt of triethanolamine, and especially preferably calcium glycerate.
[0040] Item 7: A composition according to any one of the preceding items, wherein
[0041] - The binder (a) is present in the freshly mixed mortar composition at a concentration of 180 kg / m 3 Up to 900kg / m 3 The amount exists, and / or
[0042] - The adhesive (a) has a diameter of at least 3800 cm 2 / g, preferably at least 4500cm 2 / g of Blaine surface area.
[0043] Item 8: A composition according to any of the preceding items, wherein the available aluminate from the calcium aluminate mineral phase plus the optional external aluminate source is present in the form of Al(OH)4 per 100 g of cement binder (a). - Calculated, the total amount is not more than 0.2 mol.
[0044] Item 9: A composition according to any one of the preceding items, wherein the calcium aluminate mineral phase is selected from C3A, C4AF and C12A7, in particular C3A and C4AF.
[0045] Item 10: The composition according to any one of the preceding items, wherein the cement binder (a) is Portland cement, in particular ordinary Portland cement (OPC).
[0046] Item 11: A composition according to any one of the preceding items, wherein the sulfate source (d) is a calcium sulfate source, preferably anhydrous calcium sulfate.
[0047] Item 12: A composition according to any one of the preceding items, wherein the inorganic carbonate is selected from potassium carbonate, sodium carbonate, sodium bicarbonate, lithium carbonate and magnesium carbonate; and the organic carbonate is selected from ethylene carbonate, propylene carbonate and glycerol carbonate.
[0048] Item 13: A composition according to any of the preceding items, wherein the external aluminate source (c) is selected from calcium-free aluminate sources, such as aluminum (III) salts, aluminum (III) complexes, crystalline aluminum hydroxide, amorphous aluminum hydroxide; and calcium-containing aluminate sources, such as high alumina cement, sulfoaluminate cement or synthetic calcium aluminate mineral phases.
[0049] Item 14: The composition according to any one of the preceding items, wherein the composition further comprises a dispersant, preferably, the dispersant is selected from the group consisting of:
[0050] - a comb-like polymer having a carbon-containing backbone to which are attached pendant cement anchoring groups and polyether side chains,
[0051] - a nonionic comb-like polymer having a carbon-containing backbone to which are attached pendant hydrolyzable groups which release cement anchoring groups upon hydrolysis and polyether side chains,
[0052] - Multivalent metal cations such as Al 3+ , Fe 3+ or Fe 2+ and a colloidally dispersed preparation of a polymeric dispersant, the polymeric dispersant comprising anions and / or anion generating groups and polyether side chains, and the polyvalent metal cations are present in a superstoichiometric amount, calculated as cation equivalents, based on the sum of the anions and anion generating groups of the polymeric dispersant,
[0053] - sulfonated melamine-formaldehyde condensates,
[0054] - lignin sulfonates,
[0055] -sulfonated ketone-formaldehyde condensate,
[0056] -sulfonated naphthalene-formaldehyde condensate,
[0057] - phosphonate-containing dispersants,
[0058] - phosphate-containing dispersants, and
[0059] - A mixture thereof.
[0060] Item 15: A composition according to any one of Items 3 to 14, wherein
[0061] - the alkali-activatable binder is selected from latent hydraulic binders and pozzolanic binders,
[0062] and / or
[0063] - the rock powder is a silicate or carbonate rock powder, preferably selected from limestone, dolomite, basalt and quartz powder, and / or
[0064] The inorganic pigment is selected from the group consisting of iron oxide, titanium dioxide, cobalt-chromium-aluminum-spinel and chromium(III) oxide.
[0065] Item 16: A mixed mortar composition, comprising the dry mortar composition according to any one of items 1 to 15 and water, wherein the ratio of water to cement binder (w / c) is 0.2-1.5, preferably 0.3-1.
[0066] Item 17: A product obtained from the mixed mortar composition according to Item 16.
[0067] The inventors surprisingly found that by using metal salts of polyols, such as calcium glycerate, dry mortar compositions with constant setting time while showing comparable overall strength can be obtained. In particular, a powder is formed from a liquid polyol after neutralization. When the polyol is added as a calcium salt of the polyol to the remaining components of the dry mortar composition, the dry mortar does not age and the dry mortar can be stably stored in bags for several months.
[0068] The dry mortar composition of the present invention comprises
[0069] (a) a cementitious binder comprising one or more calcium silicate mineral phases and one or more calcium aluminate mineral phases,
[0070] (b) a metal salt of a polyol, wherein the polyol is selected from a monosaccharide, an oligosaccharide, a water-soluble polysaccharide, a compound of the general formula (PI), or a dimer or trimer of a compound of the general formula (PI):
[0071]
[0072] where X is
[0073]
[0074] in
[0075] R 1 is -H, -CH3;
[0076] R 2 is -H, -CH3;
[0077] R 3 are -CH2OH, -NH2;
[0078] R 4 Yes -H, -(CH2) p CH2OH, -(CH2) s CH(OH)CH3;
[0079] m is an integer from 1 to 4;
[0080] n is an integer from 1 to 8;
[0081] p is an integer from 1 to 4;
[0082] s is an integer from 1 to 4;
[0083] (c) optionally an external source of alumina;
[0084] (d) a sulfate source;
[0085] wherein the composition comprises
[0086] (e) available aluminate from the calcium aluminate mineral phase plus optional external aluminate sources, in the form of Al(OH)4 per 100 g of cement binder a). - Calculated, the total amount of available aluminate is at least
[0087] 0.05mol;
[0088] and a molar ratio of total available aluminate to sulfate of 0.4 to 2.0;
[0089] The composition also comprises
[0090] (f) an ettringite formation controlling agent, the ettringite formation controlling agent comprising (i) glyoxylic acid, glyoxylate, hydroxycarboxylic acid or its derivatives or salts and / or glyoxylic acid derivatives and their salts; and / or mixtures thereof, and (ii) a carbonate source, wherein the carbonate source is selected from inorganic carbonates, preferably having a carbonic acid content of 0.1 g·L at 25° C. -1 or higher water solubility; organic carbonates; and mixtures thereof.
[0091] The cement binder (a) comprises one or more calcium silicate mineral phases and one or more crystalline calcium aluminate mineral phases.
[0092] Conveniently, the mineral phases are indicated herein by their cement symbols. The major compounds are indicated in the cement symbol by the oxide species: C for CaO, M for MgO, S for SiO2, A for Al2O3, $ for SO3, F for Fe2O3, and H for H2O.
[0093] Typically, calcium silicate mineral phase and calcium aluminate mineral phase constitute at least 90wt% of cement binder (a). In addition, calcium silicate mineral phase preferably constitutes at least 60wt% of cement binder (a), more preferably constitutes at least 65wt%, most preferably constitutes 65wt% to 75wt%.
[0094] Suitably, the calcium silicate mineral phase is selected from C3S (alite) and C2S (belite).The calcium silicate mineral phase primarily provides the final strength properties.
[0095] Suitably, the calcium aluminate mineral phase is selected from C3A, C4AF and C12A7, in particular C3A and C4AF.
[0096] In one embodiment, cement binder (a) is Portland cement, in particular Ordinary Portland Cement (OPC). The term "Portland cement" represents any cementitious compound containing Portland clinker, in particular CEM I within the meaning of paragraph 5.2 of standard EN 197-1. According to DIN EN 197-1, a preferred cement is Ordinary Portland Cement (OPC). The phases constituting Portland cement are mainly alite (C3S), belite (C2S), calcium aluminate (C3A), calcium aluminoferrite (C4AF) and other minor phases. Commercially available OPC may contain calcium sulfate (<7wt%) or be substantially free of calcium sulfate (<1wt%).
[0097] Suitably, the cement binder (a) of the dry mortar composition has a particle size of at least 3800 cm 2 / g, preferably at least 4500cm 2 / g, most preferably at least 5000cm 2 / g of Blaine surface area. The Blaine surface area is used as a parameter for the fineness of grind. A finer grind allows for a higher reactivity. The Blaine surface area can be determined in accordance with DIN EN 196-6.
[0098] Suitably, the amount of cement binder (a) in the dry mortar composition is in the range of 8 wt % to 50 wt %, preferably 10 wt % to 30 wt %, relative to the solid content of the dry mortar composition.
[0099] Suitably, the binder (a) is present in the freshly mixed mortar composition at a concentration of 180 kg / m 3 Up to 900kg / m 3 , preferably 180kg / m 3 Up to 600kg / m 3 The amount exists.
[0100] According to the present invention, the dry mortar composition contains (b) a salt of a polyol, wherein the polyol is selected from monosaccharides, oligosaccharides, water-soluble polysaccharides, compounds of the general formula (PI), or dimers or trimers of compounds of the general formula (PI):
[0101]
[0102] where X is
[0103]
[0104] in
[0105] R 1 is -H, -CH3;
[0106] R 2 is -H, -CH3;
[0107] R 3 are -CH2OH, -NH2;
[0108] R 4 Yes -H, -(CH2) p CH2OH, -(CH2) s CH(OH)CH3;
[0109] m is an integer from 1 to 4;
[0110] n is an integer from 1 to 8;
[0111] p is an integer from 1 to 4;
[0112] s is an integer from 1 to 4.
[0113] When the dry mortar composition contains a metal salt of a polyol, especially a calcium salt of a polyol, a dry mortar composition having a constant setting time while exhibiting comparable overall strength can be obtained.
[0114] The multivalent metal salt is selected from the group consisting of alkali metals, alkaline earth metals, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc and aluminum.
[0115] Alkaline earth metals include beryllium, magnesium, calcium, strontium, barium. In a preferred embodiment, the alkaline earth metal is calcium.
[0116] Alkali metals include lithium, sodium, potassium, rubidium, cesium, and francium.
[0117] "Polyol" is intended to represent a compound having at least two alcoholic hydroxyl groups in the molecule, for example 3, 4, 5 or 6 alcoholic hydroxyl groups. Polyols having vicinal hydroxyl groups are preferred. Polyols having at least three hydroxyl groups sequentially bonded to three carbon atoms are most preferred.
[0118] In a preferred embodiment, the polyol (b) is selected from compounds consisting only of carbon, hydrogen and oxygen and does not contain carboxyl groups (COOH) in its molecules.
[0119] In one embodiment, the polyol (b) is selected from sugars. Useful sugars include monosaccharides such as glucose and fructose; disaccharides such as lactose and sucrose; trisaccharides such as raffinose; and water-soluble polysaccharides such as amylose and maltodextrin. Monosaccharides and disaccharides, especially sucrose, are particularly preferred.
[0120] In another preferred embodiment, polyol (b) is selected from compounds consisting only of carbon, hydrogen and oxygen and contains neither carboxyl (COOH) nor carbonyl (C=O) groups in its molecule. It should be understood that the term "carbonyl" encompasses the tautomeric form of the C=O group, i.e. a pair of double-bonded carbon atoms adjacent to a hydroxyl group (-C=C(OH)-).
[0121] Compounds of formula (PI) wherein X is (P-Ia) are generally referred to as sugar alcohols. Sugar alcohols are organic compounds, usually derived from sugars, with a hydroxyl group (-OH) attached to each carbon atom. Useful sugar alcohols are mannitol, sorbitol, xylitol, arabitol, erythritol and glycerol. Of these, glycerol is particularly preferred. It is conceivable that carbonates of polyols, such as glycerol carbonate, may serve as a source of polyols.
[0122] Compounds of formula (PI) wherein X is (P-Ib) include pentaerythritol and tris(hydroxymethyl)aminomethane.
[0123] Compounds of formula (PI) wherein X is (P-Ic) include diethanolamine, triethanolamine triisopropanolamine, diisopropylamine, methyldiethanolamine and methyldiisopropanolamine.
[0124] Dimers or trimers represent compounds in which two or three molecules of the general formula (PI) are linked via ether bridges and which formally result from a condensation reaction with elimination of one or two water molecules. Examples of dimers and trimers of compounds of formula (PI) include dipentaerythritol and tripentaerythritol.
[0125] In a preferred embodiment, the calcium salt of the polyol (b) is a calcium salt of a compound of the general formula (PI) or a dimer or trimer of a compound of the general formula (PI), preferably a calcium salt of a compound of the general formula (P-Ia), more preferably calcium glycerate or a calcium salt of triethanolamine, and especially preferably calcium glycerate.
[0126] In one embodiment, the metal salt of polyol (b) is present in an amount of 0.15 wt% to 2.5 wt%, preferably 0.3 wt% to 2.5 wt%, more preferably 1.5 wt% to 2.5 wt%, relative to the amount of cement binder (a).
[0127] In one embodiment, the metal salt of the polyol (b) is present in crystalline or amorphous form.
[0128] According to the present invention, in every 100g of cement binder (a), Al(OH)4 - The dry mortar composition contains at least 0.05 mol of total available aluminate (e) calculated from the calcium aluminate mineral phase plus optional external aluminate sources. Preferably, the dry mortar composition contains at least 0.065 mol, in particular at least 0.072 mol of total available aluminate per 100 g of cement binder (a).
[0129] The best properties in terms of open time before setting and early strength development are shown when the dry mortar composition contains at least 0.05 mol of total available aluminate per 100 g of cement binder (a).
[0130] In one embodiment, in every 100 g of cement binder (a), Al(OH)4 - The dry mortar composition contains not more than 0.2 mol of total available aluminate from the calcium aluminate mineral phase plus optional external aluminate sources, calculated as above. Preferably, the dry mortar composition contains not more than 0.15 mol, in particular not more than 0.1 mol, of total available aluminate per 100 g of cement binder (a). If the cement binder contains more than 0.2 mol of total available aluminate per 100 g of cement binder (a), the open time is even shorter.
[0131] Typically, the approximate proportions of the main minerals in Portland cement are calculated by Bauer's formula, which in turn is based on the elemental composition of the clinker determined, for example, by X-ray fluorescence (XRF). This method provides the oxide composition of the element. This means that the amount of Al is reported as Al2O3. It has been found that cements with apparently the same Al2O3 content exhibit very different properties in terms of early strength and controllability through hydration control. Cement includes Al sources with very different mineralogical properties and solubility. The inventors have found that not all Al is available or readily available for the formation of ettringite. Only Al-containing mineral phases with sufficient solubility in the aqueous environment of the cement paste participate in the formation of ettringite. Other Al-containing minerals, such as crystalline aluminum oxides, for example corundum, do not form aluminates in an aqueous environment due to their limited solubility. Therefore, elemental analysis alone cannot provide reliable values for available aluminates.
[0132] Therefore, the present invention relies on Al(OH)4 - Calculated available aluminate (e). “Available aluminate” is intended to encompass aluminates that can generate Al(OH)4 - Mineral phases and Al-containing compounds. Calcium aluminate phases, such as C3A (Ca3Al2O6), dissolve in alkaline water environments to produce Al(OH)4 - and Ca 2+ ions. For the purpose of the present invention, Al(OH)4 - The concentration of mineral phases and Al-containing compounds is expressed as Al(OH)4 per 100 g of cement binder (a). - The number of mol.
[0133] It is believed that, in contrast to crystalline alumina, the common calcium aluminate mineral phase is the available aluminate source. Therefore, the amount of available aluminate in a given cement binder can be determined by a method that can distinguish the mineral phases that make up the cement binder. A useful method for this purpose is the Rietveld refinement of an X-ray diffraction (XRD) powder pattern. This software technique is used to refine various parameters, including lattice parameters, peak positions, intensities, and shapes. This allows the calculation of a theoretical diffraction pattern. Once the calculated diffraction pattern is almost identical to the data of the sample being examined, accurate quantitative information of the contained mineral phases can be determined.
[0134] Usually, Al(OH)4 can be generated in alkaline water environment - The calcium aluminate mineral phase is tricalcium aluminate (C3A), monocalcium aluminate (CA), calcium aluminate (C12A7), meteoric calcium aluminate (CA2), Q phase (C20A 13M3S3) or tetracalcium aluminoferrate (C4AF). For practical purposes, if the cement binder (a) is Portland cement, it is usually sufficient to evaluate only the following mineral phases: tricalcium aluminate (C3A), monocalcium aluminate (CA), calcium aluminate (C12A7) and tetracalcium aluminoferrate (C4AF), in particular tricalcium aluminate (C3A) and tetracalcium aluminoferrate (C4AF).
[0135] Alternatively, the amount of available aluminate can be obtained by determining the total amount of Al from the elemental composition of the cement binder (a) (e.g., by XRF) and subtracting therefrom the amount of crystalline aluminum compounds that cannot form available aluminates (as determined by XRD and Rietveld refinement). This method also takes into account amorphous soluble aluminum compounds that can form available aluminates. Such crystalline aluminum compounds that cannot form available aluminates include compounds of the chalcedony group, such as chalcedony (C2AS), compounds of the spinel group, such as spinel (MA), mullite (Al2Al2S), and quartz (C2S). 2+2x Si 2-2x O 10-x ) and corundum (Al2O3).
[0136] In one embodiment, the present invention utilizes a cement binder containing a sufficient amount of available aluminate from the calcium aluminate mineral phase (as determined by, for example, XRD analysis) to meet the amounts specified above.
[0137] Alternatively, an external aluminate source (c) may be added if the cement binder (a) itself contains an insufficient concentration of available aluminate per 100 g of cement binder (a). Thus, in some embodiments, the building composition contains an external aluminate source (c).
[0138] The external aluminate source (c) provides the available aluminate as defined above. Suitably, the external aluminate source (c) is selected from a calcium-free aluminate source, such as aluminum (III) salts, aluminum (III) complexes, crystalline aluminum hydroxide, amorphous aluminum hydroxide; and a calcium-containing aluminate source, such as high alumina cement, sulphoaluminate cement or a synthetic calcium aluminate mineral phase.
[0139] Useful aluminum (III) salts are those that readily form Al(OH)4 in an alkaline aqueous environment. - Aluminum (III) salts. Suitable aluminum (III) salts include, but are not limited to, aluminum halides, such as aluminum chloride (III) and its corresponding hydrates, amorphous aluminum oxide, aluminum hydroxide or their mixed forms, aluminum sulfate or sulfate-containing aluminum salts, such as potassium alum and its corresponding hydrates, aluminum nitrate, aluminum nitrite and its corresponding hydrates, aluminum complexes, such as aluminum triformate, aluminum triacetate, aluminum diacetate and aluminum acetate, aluminum-containing metal organic frameworks, such as aluminum fumarate, such as BasollteTMA520 and M (II) -aluminum-oxo-hydrates, such as hydrogarnet. Aluminum hydroxide (III) can be crystalline or amorphous. Preferably, amorphous aluminum hydroxide is used.
[0140] High aluminate cement refers to cement containing a high concentration (e.g., at least 30 wt%) of calcium aluminate phase. More specifically, the aluminate-type mineral phase comprises tricalcium aluminate (C3A), monocalcium aluminate (CA), mayenite (C12A7), tetracalcium aluminoferrite (C4AF), or a combination of several of these phases.
[0141] Sulphoaluminate cement has a calcium sulphoaluminate (chemical formula 4CaO.3Al2O3.SO3 or cement symbol C4A3$) content typically greater than 15 wt%.
[0142] Suitable synthetic calcium aluminate mineral phases include amorphous mayenite (C12A7).
[0143] The dry mortar composition comprises a sulfate source (d). The sulfate source is a compound capable of providing sulfate ions in an alkaline water environment. Typically, the water solubility of the sulfate source is at least 0.6 mmol·L at a temperature of 30°C. -1 The aqueous solubility of the sulfate source is suitably determined in water having an initial pH of 7.
[0144] Specifically, the molar ratio of total available aluminate to sulfate is in the range of 0.4 to 2.0, preferably 0.57 to 0.8, in particular about 0.67. This means that the mixing ratio in the composition is adjusted so that as high a proportion as possible of ettringite is formed from the available aluminate.
[0145] As previously mentioned, commercial forms of Portland cement typically contain a small amount of a sulfate source. If the inherent amount of sulfate is unknown, it can be determined by methods familiar to the skilled person, such as elemental analysis by XRF. As sulfate sources commonly used in cement production, alkaline earth metal sulfates, alkali metal sulfates or mixed forms thereof, such as gypsum, hemihydrate, anhydrite, monoglauberite, anhydrous sodium sulfate, potassium gypsum, anhydrous kaolinite, are usually crystalline, and their amounts can also be determined by XRD. When calculating the molar ratio of total available aluminate to sulfate, the inherent amount of sulfate and any added exogenous sulfate source are taken into account.
[0146] Typically, the exogenous sulfate source can be a calcium sulfate source, preferably selected from calcium sulfate dihydrate, anhydrite, α-hemihydrate and β-hemihydrate, i.e. α-calcined gypsum and β-calcined gypsum, or mixtures thereof. Preferably, the calcium sulfate source is α-calcined gypsum and / or β-calcined gypsum. Other sulfate sources are alkali metal sulfates, such as potassium sulfate or sodium sulfate.
[0147] It is contemplated that the additive may serve as a source of aluminates and sulfates, such as aluminum sulfate hexadecahydrate or aluminum sulfate octadecahydrate.
[0148] In one embodiment, the sulfate source (d) is a calcium sulfate source, preferably anhydrous calcium sulfate. The content of the calcium sulfate source is generally 3 wt% to 20 wt%, preferably 10 wt% to 15 wt%, relative to the amount of cement binder (a).
[0149] According to the present invention, the dry mortar composition contains an ettringite formation control agent (f). The ettringite formation control agent comprises (i) glyoxylic acid, glyoxylate, hydroxycarboxylic acid or its derivative or salt and / or glyoxylic acid derivative and its salt; and / or a mixture of the above substances; and a carbonate source. The carbonate source is selected from inorganic carbonates, preferably having a concentration of 0.1 g·L -1 or higher water solubility; organic carbonates; and mixtures thereof.
[0150] It is believed that component (i), i.e. glyoxylic acid, glyoxylates and / or glyoxylic acid derivatives, glyoxylates, hydroxycarboxylic acids or their derivatives or salts and / or glyoxylic acid derivatives and their salts; and / or mixtures thereof, in combination with carbonate ions, retards the formation of ettringite from the aluminate phase originating from the cement binder.
[0151] Preferably, the total amount of (i) glyoxylic acid, glyoxylates and / or glyoxylic acid derivatives, glyoxylates, hydroxycarboxylic acids or their derivatives or salts and / or glyoxylic acid derivatives and their salts; and / or mixtures thereof is present in an amount of 0.2 wt % to 2 wt %, preferably 0.3 wt % to 1 wt %, relative to the amount of cementitious binder (a).
[0152] Useful glyoxylates include alkali metal glyoxylates such as sodium glyoxylate and potassium glyoxylate.
[0153] Useful glyoxylic acid derivatives include glyoxylic acid polymers and glyoxylic acid adducts.
[0154] In one embodiment, the glyoxylic acid polymer is an amine-glyoxylic acid condensate. The term "amine-glyoxylic acid condensate" is intended to mean a condensate of glyoxylic acid and a compound containing an amino or acylamino group that can react with an aldehyde. Examples of compounds containing aldehyde-reactive amino or acylamino groups include urea, thiourea, melamine, guanidine, acetoguanamine, benzoguanamine and other acylguanamines and polyacrylamide.
[0155] Preferably, the amine-glyoxylic acid condensate is a melamine-glyoxylic acid condensate, a urea-glyoxylic acid condensate, a melamine-urea-glyoxylic acid condensate and / or a polyacrylamide-glyoxylic acid condensate. Urea-glyoxylic acid condensates are particularly preferred. Useful amine-glyoxylic acid condensates and their manufacture are described in WO 2019 / 077050, which is incorporated herein by reference.
[0156] Amine-glyoxylic acid condensates can be obtained by reacting glyoxylic acid with a compound containing an aldehyde-reactive amino group or an acylamino group. Glyoxylic acid can be used in the form of an aqueous solution or a glyoxylate, preferably an alkali metal glyoxylate. Similarly, the amine compound can be used in the form of a salt, such as a guanidine salt.
[0157] Typically, the amine compound and glyoxylic acid are reacted in a molar ratio of 0.5 to 2 equivalents, preferably 1 to 1.3 equivalents of glyoxylic acid / aldehyde-reactive amino or acylamino groups. The reaction is carried out at a temperature of 0° C. to 120° C., preferably 25° C. to 105° C. The pH value is preferably 0 to 8. The viscous product obtained in the reaction can be used as it is, adjusted to the desired solid content by dilution or concentration, or evaporated to dryness by, for example, spray drying, drum drying or flash drying.
[0158] Typically, the molecular weight of the amine-glyoxylic acid condensate is in the range of 500 g / mol to 25 000 g / mol, preferably 1000 g / mol to 10 000 g / mol, particularly preferably 1000 g / mol to 5000 g / mol.
[0159] Useful glyoxylic acid adducts are glyoxylic acid bisulfite adducts of the formula
[0160]
[0161] in
[0162] X is independently selected from H or a cation equivalent Cat a, wherein Cat is a cation, which is not particularly limited, but is preferably selected from alkali metal, alkaline earth metal, zinc, iron, ammonium or phosphonium cations or mixtures thereof, and a is 1 / n, wherein n is the valence of the cation. The glyoxylic acid bisulfite adduct can be prepared as described in WO 2017 / 212045.
[0163] Suitable hydroxycarboxylic acids or derivatives or salts thereof include α-hydroxymonocarboxylic acids or salts thereof.
[0164] Suitable α-hydroxy monocarboxylic acids or salts thereof include citric acid, tartaric acid, lactic acid, malic acid, glycolic acid, gluconic acid and salts and mixtures thereof. Sodium gluconate is particularly preferred.
[0165] The carbonate source (ii) may be an inorganic carbonate, preferably having a carbonic acid content of 0.1 g / L at 25°C. -1 The water solubility of the inorganic carbonate salt is suitably determined in water having an initial pH of 7. It should be understood that the pH at the solubility limit is higher than the initial pH.
[0166] The presence of a carbonate source ensures that the mixed water initially has a high concentration of carbonate ions. Carbonate ions are believed to be adsorbed onto the surface of the mineral phase along with glyoxylic acid, glyoxylate and glyoxylic acid derivatives.
[0167] Preferably, the carbonate source is present in an amount of 0.3 wt% to 1 wt%, preferably 0.3 wt% to 0.5 wt%, relative to the amount of cement binder (a).
[0168] The carbonate source may be an inorganic carbonate, preferably having a carbonate content of 0.1 g / L -1 or higher water solubility.
[0169] "Inorganic carbonate" is intended to mean a salt of carbonic acid, i.e., a salt containing carbonate ions (CO3 2- ) and / or bicarbonate ion (HCO) are characterized by salts.
[0170] In one embodiment, the inorganic carbonate can be suitably selected from alkali metal carbonates, such as potassium carbonate, sodium carbonate, sodium bicarbonate or lithium carbonate, and alkaline earth metal carbonates that meet the required water solubility, such as magnesium carbonate. Other suitable inorganic carbonates include carbonates of nitrogenous bases, such as guanidine carbonate and ammonium carbonate. Especially preferred are sodium carbonate and sodium bicarbonate, particularly sodium bicarbonate.
[0171] Alternatively, the carbonate source is selected from organic carbonates. "Organic carbonate" represents an ester of carbonic acid. Organic carbonates are hydrolyzed in the presence of a cement system to release carbonate ions. In one embodiment, the organic carbonate is selected from ethylene carbonate, propylene carbonate, glycerol carbonate, dimethyl carbonate, di(hydroxyethyl) carbonate or a mixture thereof, preferably ethylene carbonate, propylene carbonate and glycerol carbonate or a mixture thereof, particularly ethylene carbonate and / or propylene carbonate. Also mixtures of inorganic carbonates and organic carbonates can be used.
[0172] The weight ratio of component (i) to component (ii) is generally in the range of about 10:1 to about 1:10, preferably about 5:1 to about 1:5 or about 1:1 to about 1:4.
[0173] Preferably, the dry mortar composition of the present invention comprises a co-retarder (g), which is selected from (g-1) phosphonic acid and its salt, (g-2) polycarboxylic acid and its salt, and a mixture thereof.
[0174] Preferably, the co-retarder (g) is present in a total amount of 0.05 wt% to 1 wt%, preferably 0.05 wt% to 0.2 wt%, relative to the amount of cementitious binder (a).
[0175] Suitable phosphonic acids and salts thereof (g-1) are in particular polyphosphonic acids and salts thereof, and include 1-hydroxyethylidene-1,1-diphosphonic acid (HEDP), amino-tris(methylenephosphonic acid) (ATMP) or [[(2-hydroxyethyl)imino]bis(methylene)]-diphosphonic acid, and salts thereof and mixtures thereof. The corresponding chemical formula of the preferred diphosphonates or triphosphonates is as follows:
[0176]
[0177]
[0178] Suitable polycarboxylic acids and their salts (g-2) include phosphonoalkyl carboxylic acids, amino carboxylic acids and polymeric carboxylic acids, and their salts and mixtures thereof.
[0179] The term polycarboxylic acid used herein means a compound or polymer having two or more carboxyl groups in a molecule.
[0180] Suitable polycarboxylic acids include low molecular weight polycarboxylic acids (molecular weight, e.g., 500 or less), particularly aliphatic polycarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, fumaric acid, maleic acid, itaconic acid, citraconic acid, mesaconic acid, malic acid, tartaric acid and citric acid.
[0181] Suitable phosphonoalkyl carboxylic acids include 1-phosphonobutane-1,2,4-tricarboxylic acid, 2-phosphonobutane-1,2,4-tricarboxylic acid, 3-phosphonobutane-1,2,4-tricarboxylic acid, 4-phosphonobutane-1,2,4-tricarboxylic acid, 2,4-diphosphonobutane-1,2,4-tricarboxylic acid, 2-phosphonobutane-1,2,3,4-tetracarboxylic acid, 1-methyl-2-phosphonopentane-1,2,4-tricarboxylic acid or 1,2-phosphonoethane-2-dicarboxylic acid.
[0182] Suitable aminocarboxylic acids include ethylenediaminetetraacetic acid or nitrilotriacetic acid.
[0183] Suitable polymeric carboxylic acids include homopolymers of acrylic acid, homopolymers of methacrylic acid, polymaleic acid, copolymers such as ethylene / acrylic acid copolymers and ethylene / methacrylic acid copolymers; copolymers of acrylic acid and / or methacrylic acid with monomers containing sulfonic or sulfonic acid groups. In one embodiment, the monomers containing sulfonic or sulfonic acid groups are selected from the following groups: vinylsulfonic acid, (meth)allylsulfonic acid, 4-vinylbenzenesulfonic acid or 2-acrylamido-2-methylpropylsulfonic acid (ATBS), with ATBS being particularly preferred. One or more of the aforementioned monomers containing sulfonic or sulfonic acid groups may be contained in the copolymer.
[0184] Typically, the molecular weight of the polymeric carboxylic acid is in the range of 1000 to 30 000 g / mol, preferably 1000 to 10 000 g / mol. The molecular weight is measured by gel permeation chromatography (GPC) as indicated in detail in the experimental part.
[0185] Suitably, assuming that all carboxyl groups are in unneutralized form, the polymeric carboxylic acid or salt thereof has a carboxyl milliequivalent number of 3.0 meq / g or more, preferably from 3.0 meq / g to 17.0 meq / g, more preferably from 5.0 meq / g to 17.0 meq / g, most preferably from 5.0 meq / g to 14.0 meq / g.
[0186] Preferably, the dry mortar composition according to the present invention further comprises fines (h) having a Dv90 of less than 200 μm, preferably less than 150 μm, more preferably less than 70 μm or less than 50 μm.
[0187] DV90 (by volume) corresponds to the 90th percentile of the particle size distribution, which means that 90% of the particles have a particle size of Dv90 or less and 10% of the particles have a particle size greater than Dv90. In general, Dv90 and other values of the same type are characteristic of the particle size distribution (volume distribution) of a collection of particles or grains. If at least 90% of the particles by volume pass through a sieve with a mesh opening of 200 μm, the requirement that 90% of the particles have a size of 200 μm or less is ensured to be met. Alternatively, Dv90 can be calculated from a particle size distribution measured by static laser diffraction using a Malvern Mastersizer 2000.
[0188] The particle size distribution affects the bulk density, which in turn affects the water demand and mechanical properties of the dry mortar composition. The bulk density of the dry mortar composition, especially the bulk density of the fines, should be as high as possible to improve workability and reduce water demand. Typically, the particle size of the fines (h) ranges from 50 nm to 1 mm.
[0189] The dry mortar composition comprises fine material (h) having a Dv90 of less than 200 μm, preferably less than 175 μm, more preferably less than 150 μm, selected from alkali-activatable binders, rock powders and inorganic pigments or mixtures thereof, in a total amount of 20 to 200 parts by weight relative to 100 parts by weight of the cement binder (a).
[0190] The term "alkali-activatable binder" is intended to mean a material which sets in a cement-like manner in an aqueous alkaline environment. The term encompasses materials commonly referred to as "latent hydraulic binders" and "pozzolanic binders".
[0191] For the purposes of the present invention, a "latent hydraulic binder" is preferably a binder having a molar ratio (CaO+MgO):SiO2 of 0.8 to 2.5, in particular 1.0 to 2.0. In general, the above-mentioned latent hydraulic binder can be selected from industrial and / or synthetic slags, in particular blast furnace slag, electrothermal phosphorus slag, steel slag and mixtures thereof. A "pozzolanic binder" can generally be selected from amorphous silica, preferably precipitated silica, fumed silica and finely divided silica, frosted glass, metakaolin, aluminosilicates, fly ash, preferably lignite fly ash and hard coal fly ash, natural volcanic ashes, such as tuff, trass and volcanic ashes, calcined clay, burnt shale, rice husk ash, natural and synthetic zeolites and mixtures thereof.
[0192] The slag can be industrial slag, i.e. waste from industrial processes, or synthetic slag. The latter can be advantageous since the quantity and quality of industrial slag is not always constant.
[0193] Blast furnace slag (BFS) is a waste product of the blast furnace process. Other materials are granulated blast furnace slag (GBFS) and ground granulated blast furnace slag (GGBFS), the latter being granulated blast furnace slag that has been finely crushed. Ground granulated blast furnace slag can vary in grind fineness and particle size distribution, depending on the source and processing method, and the grind fineness here affects reactivity.
[0194] However, for the purposes of the present invention, the expression "blast furnace slag" is intended to include material resulting from all mentioned processes, grindings and quality levels (i.e. BFS, GBFS and GGBFS). Blast furnace slag generally contains 30 to 45 wt% CaO, about 4 to 17 wt% MgO, about 30 to 45 wt% SiO2 and about 5 to 15 wt% Al2O3, typically about 40 wt% CaO, about 10 wt% MgO, about 35 wt% SiO2 and about 12 wt% Al2O3.
[0195] Electrothermal phosphorus slag is a waste product of electrothermal phosphorus production. It is less reactive than blast furnace slag, and it contains about 45 to 50 wt% CaO, about 0.5 to 3 wt% MgO, about 38 to 43 wt% SiO2, about 2 to 5 wt% Al2O3, and about 0.2 to 3 wt% Fe2O3, as well as fluorides and phosphates.
[0196] Steel slag is a waste product from various steel production processes and its composition varies greatly.
[0197] Amorphous silicon dioxide is preferably X-ray-amorphous silicon dioxide, ie silicon dioxide in which no crystallinity is detected by powder diffraction. The SiO2 content of the amorphous silicon dioxide obtained according to the invention is advantageously at least 80% by weight, preferably at least 90% by weight.
[0198] Precipitated silica is obtained on an industrial scale by a precipitation process starting from water glass. Precipitated silica produced in some production processes is also known as silica gel.
[0199] Fumed silica is produced by the reaction of chlorosilanes, such as silicon tetrachloride, in a hydrogen / oxygen flame. Fumed silica is an amorphous SiO2 powder with a particle size of 5nm to 50nm and a specific surface area of 50m 2 g -1 Up to 600m 2 g -1 .
[0200] Fine silicon dioxide is a by-product of silicon production or ferrosilicon production, and is also mainly composed of amorphous SiO2 powder. The diameter of these particles is on the order of 0.1 μm. The specific surface area is on the order of 15 m 2·g -1 Up to 30m 2 ·g -1 .
[0201] Metakaolin is produced by dehydrating kaolin. At 100°C to 200°C, kaolin releases physically bound water, and at 500°C to 800°C, dehydroxylation occurs, accompanied by the collapse of the lattice structure and the formation of metakaolin (Al2Si2O7). Therefore, pure metakaolin contains about 54% by weight of SiO2 and about 46% by weight of Al2O3.
[0202] Fly ash is produced in particular during the combustion of coal in power stations. According to WO 08 / 012438, class C fly ash (lignite fly ash) contains about 10% by weight of CaO, while class F fly ash (hard coal fly ash) contains less than 8% by weight, preferably less than 4% by weight, typically about 2% by weight of CaO.
[0203] In another embodiment, the fines (h) are selected from "rock powders". Rock powders consist of finely crushed rocks and are abundant in source. Their use does not significantly increase the carbon footprint. Typically, rock powders include silicate or carbonate rock powders. Useful examples include limestone, such as ground limestone or precipitated limestone, dolomite, basalt and quartz powder.
[0204] In another embodiment, the fine material (h) is selected from inorganic pigments. Suitable inorganic pigments include iron oxide, titanium dioxide, cobalt-chromium-aluminum-spinel and chromium (III)-oxide, such as chrome green. Preferably, the inorganic pigment does not exceed 20 5wt% of the total amount of cement binder (a) and fine material (h), preferably not more than 3wt%, the remaining fine material (h) is alkali-activated binder and / or rock powder.
[0205] Although not preferred, the dry mortar composition may contain a setting accelerator such as a lithium salt, in particular lithium carbonate or lithium sulfate, as conventionally used, for example, in repair mortars and self-leveling floors. An advantageous feature of the present invention is that the early strength development of the dry mortar composition makes it possible to dispense with a lithium setting accelerator. Therefore, in a preferred embodiment, the dry mortar composition does not contain a lithium setting accelerator. This also helps to reduce the cost of the dry mortar composition, since lithium setting accelerators are very expensive ingredients.
[0206] Preferably, the dry mortar composition according to the invention further comprises at least one dispersant for an inorganic binder, in particular a dispersant for a cementitious mixture such as concrete or mortar.
[0207] Examples of useful dispersants include
[0208] - a comb-like polymer having a carbon-containing backbone to which are attached pendant cement anchoring groups and polyether side chains,
[0209] - a nonionic comb polymer having a carbon-containing backbone to which are attached pendant hydrolyzable groups which release cement anchoring groups upon hydrolysis and polyether side chains,
[0210] - Multivalent metal cations such as Al 3+ , Fe 3+ or Fe 2+ and a colloidally dispersed preparation of a polymeric dispersant, the polymeric dispersant comprising anions and / or anion generating groups and polyether side chains, and the polyvalent metal cations are present in a superstoichiometric amount, calculated as cation equivalents, based on the sum of the anions and anion generating groups of the polymeric dispersant,
[0211] - sulfonated melamine-formaldehyde condensates,
[0212] - lignin sulfonates,
[0213] -sulfonated ketone-formaldehyde condensate,
[0214] -sulfonated naphthalene-formaldehyde condensate,
[0215] - phosphonate-containing dispersants,
[0216] - phosphate-containing dispersants, and
[0217] - A mixture thereof.
[0218] Preferably, the dispersant is present in a total amount of 0.06 wt% to 0.4 wt%, preferably 0.09 wt% to 0.3 wt%, relative to the amount of cement binder (a).
[0219] Comb polymers having a carbon-containing backbone to which pendant cement anchoring groups and polyether side chains are attached are particularly preferred. Cement anchoring groups are anionic and / or anion-generating groups, such as carboxyl, phosphonic acid or phosphoric acid groups or their anions. Anion-generating groups are acid groups present in polymeric dispersants, which can be converted into corresponding anionic groups under alkaline conditions.
[0220] Preferably, the structural unit comprising anions and / or anion-generating groups is one of the general formulae (Ia), (Ib), (Ic) and / or (Id):
[0221]
[0222] in
[0223] R 1 is H, C1-C4 alkyl, CH2COOH or CH2CO-XR 3A , preferably H or methyl;
[0224] X is NH-(Cn H 2n ),O(C n H 2n ), wherein n=1, 2, 3 or 4, wherein the nitrogen atom or the oxygen atom
[0225] Bonded to CO group;
[0226] R 2 is OM, PO3M2 or O-PO3M2, provided that if R 2 is OM, then X is a chemical bond;
[0227] R is PO3M2 or O-PO3M2;
[0228]
[0229] in
[0230] R 3 is H or C1-C4 alkyl, preferably H or methyl;
[0231] n is 0, 1, 2, 3 or 4;
[0232] R 4 PO3M2 or O-PO3M2;
[0233]
[0234] in
[0235] R 5 is H or C1-C4 alkyl, preferably H;
[0236] Z is O or NR 7 ;
[0237] R 7 H, (C n H 2n )-OH, (C n H 2n )-PO3M2、(C n H 2n )-OPO3M2, (C6H4)-PO3M2, or (C6H4)-OPO3M2, and
[0238] n is 1, 2, 3 or 4;
[0239]
[0240] in
[0241] R 6 is H or C, -C, alkyl, preferably H;
[0242] Q is NR7 or O;
[0243] R 7 H, (C n H 2n )-OH, (C n H 2n )-PO3M2、(C n H 2n )-OPO3M2, (C6H4)-PO3M2, or (C6H4)-OPO3M2,
[0244] n is 1, 2, 3 or 4; and
[0245] wherein each M is independently H or a cation equivalent.
[0246] Preferably, the structural unit comprising a polyether side chain is one of the general formulae (IIa), (IIb), (IIc) and / or (IId):
[0247]
[0248] in
[0249] R 10 , R 11 and R 12 are independently H or C1-C4 alkyl, preferably H or methyl;
[0250] Z is o or S;
[0251] E is a C2-C6 alkylene group, a cyclohexylene group, a CH2-C6H 10 , 1,2-phenylene, 1,3-phenylene or 1,4-phenylene;
[0252] G is O, NH or CO-NH; or
[0253] E and G together form a chemical bond;
[0254] A is C2-C5 alkylene or CH2CH(C6H5), preferably C2-C3 alkylene;
[0255] n is 0, 1, 2, 3, 4 or 5;
[0256] a is an integer from 2 to 350, preferably from 10 to 150, more preferably from 20 to 100;
[0257] R 13 is H, unbranched or branched C1-C4 alkyl, CO-NH2 and / or COCH3;
[0258]
[0259] in
[0260] R 16 , R 17 and R 18 are independently H or C1-C4 alkyl, preferably H;
[0261] E is C2-C6 alkylene, cyclohexylene, CH2-C6H 10 , 1,2-phenylene, 1,3-phenylene or 1,4-phenylene,
[0262] Or a chemical bond;
[0263] A is C2-C5 alkylene or CH2CH(C6H5), preferably C2-C3 alkylene;
[0264] n is 0, 1, 2, 3, 4 or 5;
[0265] L is C2-C5 alkylene or CH2CH(C6H5), preferably C2-C3 alkylene;
[0266] a is an integer from 2 to 350, preferably from 10 to 150, more preferably from 20 to 100;
[0267] d is an integer from 1 to 350, preferably from 10 to 150, more preferably from 20 to 100;
[0268] R 19 is H or C1-C4 alkyl; and
[0269] R 20 is H or C1-C4 alkyl;
[0270]
[0271] in
[0272] R 21 , R 22 and R 23 are independently H or C1-C4 alkyl, preferably H;
[0273] W is 0, NR 25 or N;
[0274] Y in W=O or NR 25 1 when W=N, and 2 when W=N;
[0275] A is C2-C5 alkylene or CH2CH(C6H5), preferably C2-C3 alkylene;
[0276] a is an integer from 2 to 350, preferably from 10 to 150, more preferably from 20 to 100;
[0277] R24 is H or C1-C4 alkyl;
[0278] R 25 is H or C1-C4 alkyl;
[0279]
[0280] in
[0281] R 6 is H or C1-C4 alkyl, preferably H;
[0282] Q is NR 10 , N or O;
[0283] Y in Q=O or NR 10 1 when Q=N, and 2 when Q=N;
[0284] R 10 is H or C1-C4 alkyl;
[0285] A is C2-C5 alkylene or CH2CH(C6H5), preferably C2-C3 alkylene; and
[0286] a is an integer from 2 to 350, preferably from 10 to 150, more preferably from 20 to 100;
[0287] wherein each M is independently H or a cation equivalent.
[0288] The molar ratio of structural unit (1) to structural unit (11) varies from 1:3 to about 10:1, preferably from 1:1 to 10:1, more preferably from 3:1 to 6:1. The polymeric dispersant comprising structural units (I) and (II) can be prepared by conventional methods, for example by free radical polymerization or controlled radical polymerization. The preparation of dispersants is described, for example, in EP 0 894 811, EP 1 851 256, EP 2 463 314 and EP 0 753 488.
[0289] Many useful dispersants contain carboxyl groups, salts thereof, or hydrolyzable groups that release carboxyl groups upon hydrolysis. Preferably, the milliequivalent number of carboxyl groups contained in these dispersants (or carboxyl groups that are releasable upon hydrolysis of the hydrolyzable groups contained in the dispersant) is less than 3.0 meq / g, assuming that all carboxyl groups are in unneutralized form.
[0290] More preferably, the dispersant is selected from the following group: polycarboxylate ethers (PCEs). In PCEs, the anionic groups are carboxyl and / or carboxylate groups. PCEs are preferably obtainable by free radical copolymerization of polyether macromonomers and monomers comprising anions and / or anion-generating groups. Preferably, at least 45 mol %, preferably at least 80 mol %, of all structural units constituting the copolymer are structural units of polyether macromonomers or monomers comprising anions and / or anion-generating groups.
[0291] Another suitable class of comb polymers having a carbon-containing backbone to which are attached pendant cement anchoring groups and polyether side chains comprises the structural units (III) and (IV):
[0292]
[0293] in
[0294] T is phenyl, naphthyl or heteroaryl having 5 to 10 ring atoms, of which 1 or 2 atoms are heteroatoms selected from N, O and S;
[0295] n is 1 or 2;
[0296] B is N, NH or O, provided that if B is N, then n is 2, and if B is NH or O, then n is 1;
[0297] A is C2-C5 alkylene or CH2CH(C6H5), preferably C2-C3 alkylene;
[0298] a is an integer from 1 to 300;
[0299] R 25 H, C1-C 10 Alkyl, C5-C8 cycloalkyl, aryl or heteroaryl having 5 to 10 ring atoms, wherein 1 or 2 atoms are heteroatoms selected from N, O and S;
[0300] Wherein the structural unit (IV) is selected from the structural units (IVa) and (IVb):
[0301]
[0302] in
[0303] D is phenyl, naphthyl or a diaryl radical having 5 to 10 ring atoms, 1 or 2 of which are
[0304] a heteroatom selected from N, O and S;
[0305] E is N, NH or O, provided that if E is N, then m is 2, and if E is NH or O, then m is 1;
[0306] A is C2-C5 alkylene or CH2CH(C6H5), preferably C2-C3 alkylene;
[0307] b is an integer from 0 to 300;
[0308] M is independently H or a cation equivalent;
[0309]
[0310] in
[0311] V is phenyl or naphthyl, and is optionally substituted by 1 or two selected from R 8 , OH, OR 8 、(CO)R 8 、COOM、COOR 8 、SO3R 8 and free radical substitution with NO2;
[0312] R 7 is COOM, OCH2COOM, SO3M or OPO3M2;
[0313] M is H or a cation equivalent; and
[0314] R 8 It is C1-C4 alkyl, phenyl, naphthyl, phenyl-C1-C4 alkyl or C1-C4 alkylphenyl.
[0315] Polymers comprising structural units (III) and (IV) are obtainable by polycondensation of aromatic or heteroaromatic compounds having polyoxyalkylene groups attached to an aromatic or heteroaromatic core, aromatic compounds having carboxylic acid, sulfonic acid or phosphate moieties and aldehyde compounds such as formaldehyde.
[0316] In one embodiment, the dispersant is a nonionic comb polymer having a carbon-containing backbone to which are attached pendant hydrolyzable groups and polyether side chains, which release cement anchoring groups upon hydrolysis. Conveniently, the structural unit comprising the polyether side chains is one of the general formulas (IIa), (IIb), (IIc) and / or (IId) discussed above. The structural unit having pendant hydrolyzable groups is preferably derived from an acrylate monomer, more preferably from a hydroxyalkyl acrylate monoester and / or a hydroxyalkyl diester, most preferably from hydroxypropyl acrylate and / or hydroxyethyl acrylate. The ester functional groups will hydrolyze to (deprotonated) acid groups when exposed to water, preferably at an alkaline pH, which is provided by mixing the cement binder with water, and the resulting acid functional groups will then form a complex with the cement component.
[0317] In one embodiment, the dispersant is selected from polyvalent metal cations such as Al 3+ , Fe 3+or Fe 2+ The invention relates to a colloid dispersion preparation of a polyol, and a polymeric dispersant comprising anions and / or anion generating groups and polyether side chains. The polyvalent metal cation is present in a superstoichiometric amount, calculated as cationic equivalents, based on the sum of anions and anion generating groups of the polymeric dispersant. Such a dispersant is further described in detail in WO 2014 / 013077 A1, which is incorporated herein by reference.
[0318] Suitable sulfonated melamine-formaldehyde condensates are of a type frequently used as plasticizers for hydraulic binders (also known as MFS resins). Sulfonated melamine-formaldehyde condensates and their preparation are described, for example, in CA 2172 004 35 A1, DE 44 1 1 797 A1, US 4,430,469, US 6,555,683 and CH 686 186 and in Ullmann's Encyclopedia of Industrial Chemistry, 5th edition, volume A2, page 131 and Concrete Admixtures Handbook-Properties, Science and Technology, 2nd edition, pages 411, 412. Preferred sulfonated melamine-formaldehyde condensates encompass units of the (very simplified and idealized) formula
[0319]
[0320] wherein n is generally 10 to 300. The molecular weight is preferably in the range from 2500 to 80 000. In addition, other monomers can be incorporated into the sulfonated melamine units by condensation. Urea is particularly suitable. Furthermore, further aromatic units such as gallic acid, aminobenzenesulfonic acid, p-aminobenzenesulfonic acid, phenolsulfonic acid, aniline, aminobenzoic acid, dialkoxybenzenesulfonic acid, dialkoxybenzoic acid, pyridine, pyridinemonosulfonic acid, pyridinedisulfonic acid, pyridinecarboxylic acid and dipyridinecarboxylic acid can also be incorporated by condensation. An example of a melamine sulfonate-formaldehyde condensate is sold by Master Builders Solutions Deutschland GmbH. product.
[0321] Suitable lignin sulfonates are products obtained as by-products in the paper industry. They are described in Ullmann's Encyclopedia of Industrial Chemistry, 5th edition, volume A8, pages 586, 587. They contain units of the highly simplified and idealized formula
[0322]
[0323] The molar weight of lignin sulfonates is between 2000 g / mol and 100 000 g / mol. Typically, they are present in the form of sodium, calcium and / or magnesium salts. Examples of suitable lignin sulfonates are the Borresperse products sold by Borregaard LignoTech, Norway.
[0324] Suitable sulfonated ketone-formaldehyde condensates are products incorporating monoketones or diketones as ketone components (preferably acetone, butanone, pentanone, hexanone or cyclohexanone). Such condensates are known and are described, for example, in WO 2009 / 103579. Sulfonated acetone-formaldehyde condensates are preferred. They generally contain units of the formula (according to J. Plank et al., J. Appl. Poly. Sci. 2009, 2018-2024):
[0325]
[0326] wherein m and n are typically each 10 to 250, M is an alkali metal ion such as Na, and the ratio of m:n is typically in the range of about 3:1 to about 1:3, more particularly about 1.2:1 to 1:1.2. In addition, other aromatic units such as gallic acid, aminobenzenesulfonic acid, p-aminobenzenesulfonic acid, phenolsulfonic acid, aniline, aminobenzoic acid, dialkoxybenzenesulfonic acid, dialkoxybenzoic acid, pyridine, pyridinemonosulfonic acid, pyridinedisulfonic acid, pyridinecarboxylic acid, pyridinedicarboxylic acid may also be incorporated by condensation. An example of a suitable sulfonated acetone-formaldehyde condensate is the Melcret K1 L product sold by Master Builders Solutions Deutschland GmbH.
[0327] Suitable sulfonated naphthalene-formaldehyde condensates are products obtained by sulfonation of naphthalene and subsequent polycondensation with formaldehyde. They are described in references including Concrete Admixtures Handbook-Properties, Science and Technology, 2nd edition, pages 411-413; and Ullmann's Encyclopedia of Industrial Chemistry, 5th edition, volume AB, pages 587, 588. They contain units of the formula
[0328]
[0329] Typically, molar weights (Mw) between 1000 g / mol and 50 000 g / mol are obtained. In addition, other aromatic units such as gallic acid, aminobenzenesulfonic acid, para-aminobenzenesulfonic acid, phenolsulfonic acid, aniline, aminobenzoic acid, dialkoxybenzenesulfonic acid, dialkoxybenzoic acid, pyridine, pyridinemonosulfonic acid, pyridinedisulfonic acid, pyridinecarboxylic acid and pyridinedicarboxylic acid can also be incorporated by condensation. An example of a suitable sulfonated β-naphthalene-formaldehyde condensate is the Melcret 500L product sold by Master Builders Solutions Deutschland GmbH.
[0330] Typically, phosphonate-containing dispersants contain phosphonate groups and pendant polyether groups.
[0331] Suitable phosphonate-containing dispersants are those according to the formula
[0332] R-(OA 2 ) n6 -N-[CH2-PO(OM 3 2)2]2
[0333] in
[0334] R is a Hora hydrocarbon residue, preferably C1-C 15 Alkyl radicals,
[0335] A 2 Independently for C2-C 18 Alkylene, preferably ethylene and / or propylene, most preferably ethylene,
[0336] n6 is an integer from 5 to 500, preferably from 10 to 200, most preferably from 10 to 100, and
[0337] M 3 is H, alkali metal, 1 / 2 alkaline earth metal and / or amine.
[0338] The dry mortar building composition may further comprise at least one aggregate.
[0339] The term "aggregate" is understood to refer to filler material, i.e., an inert material that does not substantially form hydration products. Aggregates can be selected from quartz, sand, marble (e.g. crushed marble), glass balls, granite, basalt, limestone, sandstone, calcite, marble, serpentine, travertine, dolomite, feldspar, gneiss, alluvial sand, and mixtures thereof. The packing density of the aggregates should be as high as possible, and their particle size distribution ideally constitutes a more complete type of screening curve.
[0340] Aggregates can be classified by particle size. Fine aggregates (such as sand) typically have a particle size distribution of 150 μm to 5 mm. Coarse aggregates typically have a particle size distribution greater than 5 mm.
[0341] The dry mortar composition can be obtained by mixing a powdered component C containing a cement binder (a) and a sulfate source (d), components (i) and (ii) with a calcium salt of a polyol (b). An optional external aluminate source (c) is contained in component C. The calcium salt of a polyol is preferably obtained by reacting a polyol with a calcium compound (e.g. calcium oxide or calcium hydroxide).
[0342] The present invention also relates to a mixed mortar composition comprising the dry mortar composition according to the present invention and water. Preferably, the ratio of water to cement binder (a) is 0.2-1.5, preferably 0.3-1, more preferably 0.3-0.7, and most preferably 0.3-0.5.
[0343] In addition to the dry mortar composition, the mixed mortar composition may comprise concrete or mortar. The term "mortar" or "mortar" represents a cement paste to which fine aggregate (i.e., aggregates with a diameter between 150 μm and 5 mm (e.g., sand)) and optionally very fine aggregate are added. Mortar is a sufficiently low viscosity mixture for filling voids or gaps. The mortar viscosity is high enough to support not only the weight of the mortar itself, but also the weight of masonry placed on it. The term "concrete" represents a mortar to which coarse aggregate (i.e., aggregates with a diameter greater than 5 mm) is added.
[0344] The mixed mortar composition may be provided in the form of a dry mix to which water is added on site to obtain the mixed mortar building composition.
[0345] The mixed mortar composition can be obtained by mixing a powdered component C containing a cement binder (a) and a sulfate source (d) and a liquid aqueous component W, wherein ingredients (i) and (ii) are contained in component C. The calcium salt of a polyol (b) is premixed with component C. The optional external aluminate source (c) is preferably contained in component C or component W. The dispersant is contained in one or both of component C and component W.
[0346] The order of addition of the optional ingredient (h) (a fine material) depends primarily on the water content of ingredient (h). When ingredient (h) is provided in a substantially anhydrous form, it can be conveniently included in component C. Otherwise, it is more common to premix ingredient (h) with component C and subsequently blend component C.
[0347] This mixing arrangement prevents the direct formation of ettringite (which would occur if the cement binder (a) were exposed to water without the presence of components (i) and (ii)), which can effectively control the formation of ettringite.
[0348] The present invention also relates to a product obtained by the mixed mortar composition of the present invention.
[0349] In the context of the present invention, the article is preferably a hardened product.
[0350] The article can be obtained by the following method. The method for preparing the article comprises a step of drying the mixed mortar composition according to the present invention. The drying step can be an active or passive drying step. When the drying step is an active drying step, the drying is carried out at a temperature of up to 90°C, preferably 30°C to 55°C. When the drying step is a passive step, the mixed mortar composition is dried due to hydration and evaporation of water.
[0351] The present invention is further illustrated by the following figures and examples.
[0352] method
[0353] Test Procedure - Setting Time
[0354] The setting time is determined according to DIN 196-3 using a 300 g Vicat needle. The start of setting is reached when the needle stops 3 mm above the glass plate. The end of setting is reached when the needle stops 38 mm above the glass plate. The time is in minutes.
[0355] Testing Procedure - General Strength Development
[0356] The adjusted mortar mixtures were each filled into a mortar steel prism (16 / 4 / 4 cm), and after 3 hours at a temperature of 20° C. and a relative humidity of 65%, hardened mortar prisms were obtained.
[0357] According to DIN EN 13892-1, the hardened mortar prisms were demoulded 5 h, 1 d and 7 d after mixing and the compressive strength was measured. Example
[0358] substance :
[0359] For the Examples and Comparative Examples, the following materials were used:
[0360] Retarder 1: Retarder 7 indicated in Table 1 of WO 2019 / 077050 was used as retarder 1
[0361] Dispersant 1: The dispersant is a polycarboxylic acid ether, more specifically a copolymer of 4-hydroxybutyl monovinyl ether ethoxylated with an average of 64 mol of ethylene oxide and acrylic acid in a ratio of 1 / 10 (Dispersant 1 in WO 2019 / 077050)
[0362] Cement: CEM I 52.5N (available aluminum, as Al(OH)4 - Calculation: 0.0865 mol / 100 g cement; Blaine surface area: 3401 cm2 / g; CaSO4 amount / 100g cement: 0.0204mol)
[0363] Additive Package :
[0364] Defoamer: Vinapor DF 9010F (commercially available from BASF Construction Additive GmbH, Trostberg, Germany)
[0365] Viscosity modifier: Starvis 3040F (commercially available from BASF Construction Additive GmbH, Trostberg, Germany)
[0366] Prepare calcium glycerate as follows:
[0367] 1.5 mol equivalent of glycerol was added to the container. 1 mol equivalent of Ca(OH)2 was added. The suspension was mixed and then heated to 80°C. The solid obtained after 7 h was cooled and ground into a fine powder and analyzed by IR spectroscopy and XRD.
[0368] Table 1: Dry mortar composition
[0369]
[0370] Preparation of dry mortar :
[0371] Glycerol or calcium glycerate was added to the dry mortar composition indicated in Table 1. The dry mortar was produced by thoroughly mixing the powder additives.
[0372] Comparative Example 1 :
[0373] Before mixing all components together, spray 1.145 liquid glycerin onto the cement.
[0374] Comparative Example 2 :
[0375] Before mixing all the components together, 1.145 g of liquid glycerin was sprayed onto the limestone powder.
[0376] Example 1 :
[0377] Before all components were mixed together, 1.627 g of calcium glycerate (mol equivalent of 1.145 g glycerol) were added in powder form.
[0378] The dry mortar was used within 2 h after mixing or stored for periods of 2 and 15 days. For storage, 1.0 L buckets were filled with 1.4 kg of dry mortar and then sealed airtight. These sealed buckets were stored at 21 °C for 2 and 15 days.
[0379] Production of mortar :
[0380] For the production mortar, 190.96 g of water were added to the prepared dry mortar. The mortar was mixed according to DIN EN 196-1. 5 minutes after mixing the water and dry mortar components, the flow was measured with a Haegermann cone according to DIN EN 1015-3. The flow values are presented in cm in Table 2.
[0381]
[0382] It can be seen that the setting time of the experiment of the present invention fluctuates within the experimental error range (+ / -10%) of the Vicat experiment. The setting time in the comparative example is significantly reduced, resulting in a reduction of 50% in the setting time after 15 days. This significant reduction in setting time is an obstacle to the production of dry mortar and limits its applicability.
[0383] Therefore, the inventive dry mortar composition of Example 1 exhibits a constant setting time while showing comparable overall strength.
Claims
1. A dry mortar composition, comprising (a) a cementitious binder comprising one or more calcium silicate mineral phases and one or more calcium aluminate mineral phases, (b) a metal salt of a polyol, wherein the polyol is selected from a monosaccharide, an oligosaccharide, a water-soluble polysaccharide, a compound of the general formula (PI), or a dimer or trimer of a compound of the general formula (PI): where X is in R 1 Yes -H, -CH 3 ; R 2 Yes -H, -CH 3 ; R 3 Yes-CH 2 OH, -NH 2 ; R 4 is -H, -(CH 2 ) p CH 2 OH, -(CH 2 ) s CH(OH)CH 3 ; m is an integer from 1 to 4; n is an integer from 1 to 8; p is an integer from 1 to 4; s is an integer from 1 to 4; (c) optionally an external source of alumina; (d) a sulfate source; wherein the composition comprises (e) available aluminate from said calcium aluminate mineral phase plus said optional external aluminate source, expressed as Al(OH) 4 - Calculated, the total amount of available aluminate is at least 0.05 mol; and a molar ratio of total available aluminate to sulfate of 0.4 to 2.0; The composition also comprises (f) an ettringite formation controlling agent, the ettringite formation controlling agent comprising (i) glyoxylic acid, glyoxylate, hydroxycarboxylic acid or its derivatives or salts and / or glyoxylic acid derivatives and their salts; and / or mixtures thereof, and (ii) a carbonate source, wherein the carbonate source is selected from inorganic carbonates, preferably having a carbonic acid content of 0.1 g·L at 25° C. -1 or higher water solubility; Organic carbonates; and mixtures thereof.
2. The composition according to claim 1, wherein the composition further comprises a co-retarder (g), the co-retarder being selected from (g-1) phosphonic acid and its salts, (g-2) polycarboxylic acid and its salts; and A mixture of them.
3. The composition according to claim 1 or 2, wherein the composition further comprises (h) fine material having a Dv90 of less than 200 μm, preferably less than 150 μm, selected from alkali-activatable binders, rock powders and inorganic pigments or mixtures thereof, in a total amount of 20 to 200 parts by weight relative to 100 parts by weight of cement binder (a).
4. The composition according to any one of the preceding claims, wherein the metal salt of the polyol (b) is present in an amount of 0.15 wt% to 2.5 wt% relative to the amount of the cement binder (a).
5. The composition according to any one of the preceding claims, wherein the metal salt of the polyol (b) is present in crystalline or amorphous form.
6. A composition according to any one of the preceding claims, wherein the metal salt (b) of the polyol is a calcium salt of a compound of the general formula (PI) or a dimer or trimer of a compound of the general formula (PI), preferably a calcium salt of a compound of the general formula (P-Ia), more preferably calcium glycerate or a calcium salt of triethanolamine, and especially preferably calcium glycerate.
7. A composition according to any one of the preceding claims, wherein - The binder (a) is present in the freshly mixed mortar composition at a concentration of 180 kg / m 3 Up to 900kg / m 3 , preferably 180kg / m 3 Up to 600kg / m 3 The amount exists, and / or - The adhesive (a) has a diameter of at least 3800 cm 2 / g, preferably at least 4500cm 2 / g of Blaine surface area.
8. A composition according to any one of the preceding claims, wherein the available aluminate from the calcium aluminate mineral phase plus the optional external aluminate source is present in the form of Al(OH) per 100 g of cement binder a). 4 - Calculated, the total amount is not more than 0.2 mol.
9. The composition according to any one of the preceding claims, wherein the calcium aluminate mineral phase is selected from C3A, C4AF and C12A7, in particular C3A and C4AF.
10. The composition according to any one of the preceding claims, wherein the cementitious binder (a) is Portland cement, in particular Ordinary Portland Cement (OPC).
11. A composition according to any one of the preceding claims, wherein the sulfate source (d) is a calcium sulfate source, preferably anhydrous calcium sulfate.
12. A composition according to any one of the preceding claims, wherein the inorganic carbonate is selected from potassium carbonate, sodium carbonate, sodium bicarbonate, lithium carbonate and magnesium carbonate; and the organic carbonate is selected from ethylene carbonate, propylene carbonate and glycerol carbonate.
13. A composition according to any one of the preceding claims, wherein the exogenous aluminate source (c) is selected from calcium-free aluminate sources, such as aluminum (III) salts, aluminum (III) complexes, crystalline aluminum hydroxide, amorphous aluminum hydroxide; and calcium-containing aluminate sources, such as high-alumina cement, sulphoaluminate cement or synthetic calcium aluminate mineral phases.
14. A mixed mortar composition, comprising the dry mortar composition according to any one of claims 1 to 13 and water, wherein the quantitative ratio (w / c) of water to cement binder is 0.2-1.5, preferably 0.3-1.
15. A product obtained from the mixed mortar composition according to claim 14.
Citation Information
Patent Citations
Sulphonated amine aldehyde condensate, used as cement super:plasticiser
CH686186A5
Sulphanilic acid-contg. melamine-formaldehyde] condensate prepn.
DE4411797A1
Copolymers based on insaturated dicarboxylic acid-derivatives and oxyalkylenglycol-alkenylethers
EP0894811A1
Preparation of comb polymers by esterification
EP2463314A1
Process for preparing highly concentrated aqueous solutions of low viscosity of melamine / aldehyde resins
US4430469A
